EPIDEMIOLOGICAL SURVEILLANCE AND ACTIONS OF THE OFFICIAL VETERINARY SERVICE FOR THE PREVENTION AND CONTROL OF EQUINE INFECTIOUS ANEMIA IN THE STATE OF GOIÁS, BRAZIL - Margarida, Luiz Henrique Batista; Taveira, Rodrigo Zaiden; Coelho, Karyne Oliveira; Neto, Osvaldo José da Silveira (Seven Editora, 2024)
Equine Infectious Anemia (EIA) is one of the main diseases that affect equids. Its prevention, control or even eradication are among the main objectives established by the National Equine Health Program (PNSE). The state of Goiás is an important national reference in equine breeding. Equids in general generate financial foreign exchange for Brazil, in the order of billions of reais annually and an estimated generation of jobs, indirectly, above two million employed people. Goiás has an equine population of over 380 thousand animals. Equine farming has direct interference in the most diverse Brazilian communities, whether at work, sport, leisure or health. Numerous centers for training, breeding and concentration of equids are present throughout the country. Infection occurs by transmission of blood from infected to uninfected horses. The diagnosis of EIA is made by the AGID test. It is estimated that only 10% of the equine population has been tested and that the prevalence in Brazil and South America ranges from 2-3%. In 2018, Goiás had 17 anemia outbreaks completed and another 33 remain pending. EIA is a disease that has no treatment or vaccine with wide efficacy. In order for blood serum to be collected, the professional in charge must be accredited by the SVO (Official Veterinary Service). Acquiring animals with negative tests for EIA, using disposable needles, isolation of positive animals and the sacrifice or sanitary slaughter of HIV-positive people, are among the main prophylaxis measures to be taken. Considering the importance and relevance of this disease, the objective of this work is to review the literature of the most diverse concepts in animal epidemiology and health defense, focused on the side of disseminating and contributing to the execution of the actions proposed by the PNSE, both by the SVO, and by the owners, breeders and professionals who work in equine farming,  putting into practice what is determined by the current legislation. Animal health surveillance is one of the most demanding points for the control or even the eradication of diseases in production animals. DOI:https://doi.org/10.56238/sevened2024.037-006